NFIL3/Tim3 axis regulates effector Th1 inflammation in COPD mice - Ke, Junyi; Huang, Shu; He, Zhixiong; Lei, Siyu; Lin, Shiya; Li, Yinying; Li, Qiuming; Huang, Hui; Huang, Hongchun; Qin, Huajiao; Duan, Minchao (Frontiers in Immunology, 2024)
IFN-γ+CD4+ cells (type 1 helper T cells, Th1) represent a critical component of the inflammatory environment in the lungs of chronic obstructive pulmonary disease (COPD). Identifying influencing factors related to COPD-associated Th1 cells will enhance our understanding of the inflammatory mechanisms involved and facilitate the development of targeted interventions. In this study, we describe T-cell immunoglobulin and mucin-domain containing-3 (Tim3) as a key gene regulating COPD-associated Th1 cells. Our findings indicate that Havcr2 expression gradually increases during CD4+ T cell activation in COPD mice, with Tim3 being highly expressed on both CD4+ T cells and Th1 cells. Notably, the knockout of HAVCR2 further promotes the infiltration of CD4+ T cells and the expression of IFN-γ in the lungs, resulting in a more severe emphysema phenotype, although itdoes not significantly affect TNF-α expression. Additionally, NFIL3, an upstream regulator of Tim3, is also highly expressed in the CD4+ T cells of COPD mice. Mice with NFIL3 knockout exhibit phenotypes similar to those of HAVCR2 knockout mice, along with a significant downregulation of Tim3 expression. In vitro, we simulated the activation process by polarizing primary CD4+ Tn cells from COPD mice and observed that NFIL3/Tim3 expression was significantly upregulated following Th1 polarization. In summary, our study demonstrates that the NFIL3/Tim3 axis plays a role in Th1 imbalance in the lungs of COPD by inhibiting Th1 differentiation.